Variation in essential oil composition of Leonotis leonurus, an important medicinal plant in South Africa. (February 2017) - Nsuala, Baudry N.; Kamatou, Guy P.; Sandasi, Maxleene; Enslin, Gill; Viljoen, Alvaro
Abstract: Leonotis leonurus widely used by traditional healers in southern Africa for treatment of various ailments, is well known for its reported psychoactive properties. The present study was undertaken to investigate the variation in essential oil composition between geographically distinct populations of L. leonurus in South Africa using gas chromatography. Plant material ( n  = 50) was collected from three provinces of South Africa. Essential oils of the aerial parts were obtained by hydrodistillation and analysed using one and two dimensional gas chromatography. Twenty-six compounds accounted for more than 80% of the total composition of the oil. Eight major constituents in the oil, representing about 50% of the total oil composition, were identified by both GC–MS–FID and GCxGC–ToF–MS. These major compounds were trans -β-ocimene (0.1–5.0%), cis -β-ocimene (0.1–31.5%), β-caryophyllene (0.3–15.0%), caryophyllene oxide (0.1–5.0%), α-humulene (0.4–18.2%), γ-elemene (0.4–10.6%), α-cubebene (0.2–12.0%) and germacrene D (0.1–22.1%). Marked similarities exist in the essential oil composition between populations; differences are mostly quantitative when determined by GC–MS–FID, while GCxGC–ToF–MS data reveals both quantitative and qualitative differences. Untargeted multivariate analysis was performed using SIMCA-P + 14.0 PCA and OPLS-DA methods, identifying two distinct clusters, inland and coastal populations. Highlights: Geographical variation in essential oil composition of L.leonurus . Eight major constituents, identified by both GC–MS–FID and GCxGC–ToF–MS. Mostly quantitative differences using the GC–MS–FID method. GCxGC–ToF–MS data revealed both quantitative and qualitative differences. Chemomteric analysis revealed two distinct clusters, inland and costal populations.